Lithological diversity and age of kames near Suchedniów (Kielce Upland) - Kalicki, Tomasz; Przepióra, Paweł; Jabłoński, Michał; Frączek, Marcin; Podrzycki, Łukasz (Acta Universitatis Lodziensis. Folia Geographica Physica, 2022)
The kame hills and terraces located in the Suchedniów Plateau (northern part of the Kielce Upland) were the subject of research in the 1970s. In 2019, further study was started using new methods to determine the age and genesis of the sediments that build these forms. Varied hypsometry, with hills and depressions, divided the advanced ice sheet into two lobes. During deglaciation in the inter-lobe part, there was a large variability of sedimentation conditions (5 accumulation members in KR II and 4 in KR I profiles). It was resulted in the higher position (KR II) of fluvioglacial kames with dominant of sand and gravel sediments not covered with moraine. The lower (KR I), complex kames were formed, composed of alternately occurring accumulation members of finer sediments (limnoglacial kames) and coarser – sand-gravel (fluvioglacial kames) covered with ablation moraine with erratics. These forms were created during areal deglaciation and the melting of blocks of dead ice. The rate of this process was variable, and it lasted from several dozen to several thousand years, which is confirmed by the obtained TL dates, despite the appearing inversions. The Pleistocene fluvial terrace (PK 1) and the Holocene alluvia in the bottom of the Kamionka valley ware cut into kames and kame terraces sediments. Wzgórza i terasy kemowe położone na Płaskowyżu Suchedniowskim (północna część Wyżyny Kieleckiej) były przedmiotem badań w latach 70. XX wieku. W 2019 r. rozpoczęto nowymi metodami dalsze badania w celu określenia wieku i genezy osadów budujących te formy. Kemy powstały podczas zlodowaceń środkowopolskich (MIS 6), ok. 175–137 tys. lat temu. Urozmaicona hipsometria, ze wzgórzami i obniżeniami, spowodowała rozdzielenie wkraczającego lądolodu na dwa loby. W trakcie deglacjacji w części międzylobowej występowała duża zmienność warunków sedymentacji (5 poziomów akumulacji w profilach KR II i 4 w KR I). Spowodowało to wyższe położenie (KR II) kemów wodnolodowcowych z przewagą osadów piaskowo-żwirowych nieprzykrytych moreną. ...